EFFECTIVENESS OF OBSERVATION OF CHILDREN WITH BRONCHIAL ASTHMA AND EVALUATION OF THEIR QUALITY OF LIKE BY ALLERGOLOGIST - N.A. Ilyenkova; I.P. Artyukhov; L.V. Stepanova; A.V. Shul'min ("Paediatrician" Publishers LLC, 2010)
(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):168-170)